RESULTS OF THE STUDY OF IMMUNOLOGICAL CHANGES IN COMPLEX SURGICAL TREATMENT OF BRONCHIECTASIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Lack of immunity of the body against bacterial infection is the main condition for the development of bronchiectasis. In addition, many patients have no clear cause and are described as idiopathic. The study investigated the improvement of postoperative clinical results using methods of immunostatus correction in the complex surgical treatment of bronchiectasis. 118 patients treated for bronchiectasis in 2019-2023 participated in the study. The results of the study showed that the use of immunotherapy in combination with conventional treatment in complex surgical treatment of patients with bronchiectasis leads to high efficiency.